Evaluation of solitary thyroid nodule by clinical presentation, fine needle aspiration cytology and thyroid scan - Surriah, Mohammed Hillu; Bakkour, Amine Mohammed; Jallod Al-Asadi, Riad Rahman; Majeed, Laith Qauis (International Surgery Journal, 2019)
Background: The solitary thyroid nodule, defined as a palpable discrete swelling within an otherwise apparently normal gland, is usually a benign lesion. However, patients and physicians alike are typically concerned about the possibility of thyroid cancer. This study describes a strategy for the treatment of clinically euthyroid patients who have a solitary thyroid nodule that prevents unnecessary testing while identifying the few patients who require therapy. Methods: This is a prospective study of randomly selected patients with clinically palpable, solitary thyroid nodule diagnosed and treated at Al-Karama Teaching Hospital from September 2015 till December 2018. Initially 176 patients were diagnosed by clinical examination to have solitary thyroid nodule but after investigation and operative finding, 42 patients were found to have multinodular goiter and all excluded from the study. Results: All the 134 patients included in the study (21 males and 113 females) have been evaluated by clinical examination; thyroid scan and fine needle aspiration, ultrasound and the results of the evaluation have been correlated with operative histologic diagnosis. The study was undertaken to obtain information on the usefulness of the above measures for predicting or ruling out malignancy in solitary thyroid nodule. Conclusions: The incidence of malignancy seems to be higher among male, presented with hard nodule at palpation, those associated with hoarseness or palpable cervical lymph nodes. A cytological diagnosis of malignant tumor is reliable and provides sufficient basis of definitive surgery for thyroid cancer.